Os gêneros discursivos e a produção escrita nos livros didáticos de inglês - Mansur Júnior, Jonadab (2013)
Works using discursive genres to check about written productions for learning English classroom are not recent. Since the requirements of the official documents for teaching and learning a Modern Foreign Language (MFL) in Brazil National Curriculum Parameters (PCN) in 1998, for the fourth and third cycles of Elementary Education (EE), and in National Textbook Program (PNLD), in 2011, this skill becomes a reason of study for English language teachers and researchers. Therefore, based on the perspective that every utterance is a link in the chain of discursive communication, Bakhtin (2010), we analyzed the work with discursive genres observing the treatment given to the activities of written productions in English textbooks (ET) 9th year of EE. Our aim was to interpret as proposed in discursive genres work with writing in ET. Our research was guided by social cognitive approach in the philosophy of language in view of Marcuschi (2005) and socio-philosophical conceptions of Habermas (2002). We also based on the sociodiscursive theory of Bakhtin (2010) and socio-interacionist approach based on conceptions of authors like bronckart (1999), B. Marcuschi & Cavalcante (2005) and Costa Val (2003). The research corpus was composed of two student ET 9th year of EE. We listed categories of content analysis to the selected discursive genres; we decided to establish these categories on the basis of the proposed PNLD 2011 for the conditions of written productions and Costa Val (2003). The research result showed us the importance of a greater systematization, in EE, regarding the conditions of productions of discursive genres to work with writing skill, and also provides relevant guidance on the conduct of activities in the didactic sequences proposed in the ET.